Peran Sosial Media Instagram Sebagai Media Komunikasi Bisnis Dalam Peningkatan Penjualan Perusahaan Mangkok Manis - Framuditya Bagas Saputra; Amyra Syalsabila; Yurni Fadhillah; Ricky Firmansyah (Institut Nalanda, 2023)
This study aims to analyze the role of social media Instagram as a medium of business communication in increasing sales at the Mangkok Manis company in Cihampelas, Bandung. This research process uses qualitative methods with a case study approach. In-depth interviews are a technique for collecting data, the interviews conducted are by interviewing the operational managers of the Mangkok Manis company and analyzing social media content. The results of the study show that Instagram is less influential in expanding market reach and increasing sales. In its marketing strategy, the Mangkok Manis company utilizes features such as Instagram Stories and Instagram Reels to promote its products. Apart from that, interaction with customers through Instagram Direct Messages is also very important to increase customer loyalty and build stronger relationships with them, but the results are indeed unsatisfactory in terms of increasing sales because the types of products they market are not suitable for long distances. delivery, but quite influential. in terms of increasing the popularity of the company. These findings indicate that the use of social media Instagram as a medium of business communication does not help Mangkok Manis to increase its sales.